Pemanfaatan Ampas Tahu Menjadi Snack Tofstick Sebagai Usaha untuk Pemanfaatan Limbah Ampas Tahu di Kelurahan Oi Mbo Kota Bima - Ernawati, Sri; Faturrahman, Muhammad; Adwiyah, Rabiahtun; Wulandari, Putri; Dwiaryanti, Ririn (CV. IRA PUBLISHING, 2024)
This community service project was conducted in Oi Mbo Village, Rasanae Timur District, Bima City. In this area, tofu dregs are primarily used as animal feed despite their potential to be processed into value-added food products. Rich in protein, fat, and water, tofu dregs have been limited to use as livestock feed, tempe gumbos ingredients, and crackers, with a minimal economic impact on the community. This activity aimed to train the community to process tofu dregs into Tofstick snacks with improved packaging and branding. The methods included preliminary surveys, program socialization, training, and evaluation. The results demonstrated that tofu dregs could be transformed into Tofstick snacks with broad market potential, providing economic value through innovation and creativity.